Base material with deep ultraviolet transmission type transparent electrode and method for manufacturing base material with deep ultraviolet transmission type transparent electrode

The development of a Ta-doped SnO2 transparent electrode on sapphire or aluminum nitride substrates addresses low UV-C transmittance, achieving high transparency and carrier densities for improved UV-C applications.

JP2025005832APending Publication Date: 2025-01-17TOKYO METROPOLITAN PUBLIC UNIVERSITY CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023106223
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing transparent conductive compositions exhibit low transmittance to deep ultraviolet rays (UV-C) with wavelengths of 280 nm or less, limiting their effectiveness in applications such as sterilization and air purification.

Method used

A deep ultraviolet light-transmitting transparent electrode-attached base material is developed, comprising a transparent base material, such as sapphire or aluminum nitride, with a transparent oxide layer made of SnO2 doped with Ta, where the Ta content ranges from 0.8 to 7.0 atomic % relative to the sum of Sn and Ta, and is formed using a pulsed laser deposition method.

Benefits of technology

The solution achieves high transparency to deep UV rays, with carrier densities exceeding 4.5×10^20 cm^-3 and transmittance of 30% or more at 280 nm, enhancing the efficiency of UV-C applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005832000001_ABST
    Figure 2025005832000001_ABST
Patent Text Reader

Abstract

To provide a base material with a deep ultraviolet transmission type transparent electrode having high permeability to deep ultraviolet, and a method for manufacturing the base material with the deep ultraviolet transmission type transparent electrode.SOLUTION: A base material with a deep ultraviolet transmission type transparent electrode includes a transparent base material and a transparent oxide layer formed on the transparent base material. The transparent base material is any base material selected from the group consisting of a sapphire base material, an aluminum nitride base material and a base material constituted of a mixed crystal of aluminium nitride and gallium nitride. The transparent oxide layer consists of metal oxide having SnO2 as a main component and including a Ta element. An amount of the Ta element of the metal oxide is 0.8 atom% or more and 7.0 atom% or less to the total of an Sn element and the Ta element of the metal oxide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a substrate with a deep ultraviolet light-transmitting transparent electrode and a method for producing a substrate with a deep ultraviolet light-transmitting transparent electrode. [Background technology]

[0002] Transparent electrodes having transparent conductive compositions are used in display devices such as touch panels and displays, light control devices such as smart windows, light emitting devices such as LEDs, light receiving devices such as solar cells, etc. With the widespread use of the above devices, there is a demand for the development of transparent conductive compositions having properties suitable for each application. For example, there is a demand for the development of transparent conductive compositions for ultraviolet light in order to improve the efficiency of ultraviolet light devices.

[0003] Non-Patent Document 1 discloses that a thin film composed of a transparent conductive composition in which tin dioxide is doped with tantalum is formed on an r-plane sapphire substrate by metal organic chemical vapor deposition (MOCVD). The transparent conductive composition disclosed in Non-Patent Document 1 has a ratio of Ta element to Sn element of 0 to 8 atomic %, and when the ratio of Ta element to Sn element is 0 to 8 atomic %, the maximum carrier density is 3.0 to 4.0 × 10 20 cm -3 The results show that the transparent conductive composition exhibits high transmittance to ultraviolet rays (UV-B) with wavelengths of 280 to 320 nm.

[0004] Non-Patent Document 2 discloses that a thin film composed of a transparent conductive composition in which tin dioxide is doped with antimony (Sb) is formed on an r-plane sapphire substrate by molecular beam epitaxy. Non-Patent Document 2 discloses that the transparent conductive composition exhibits high transmittance to ultraviolet rays with wavelengths of 300 nm to 400 nm.

[0005] Non-Patent Document 3 discloses that a thin film containing (111)-oriented indium tin oxide (ITO) as a transparent conductive composition is formed on a c-plane sapphire substrate by MOCVD. Non-Patent Document 3 discloses that the transparent conductive composition has high transmittance, with average transmittances of 94% and 74% for ultraviolet rays with wavelengths of 315 to 400 nm (UV-A) and ultraviolet rays with wavelengths of 280 to 315 nm (UV-B), respectively. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] “UV-vis transparent conducting Ta-doped SnO2 epitaxial films grown by metal-organic chemical vapor deposition”, He et al., Mater. Res. Bull. (2019), doi: 10.1016 / j.materresbull.2019.05.013 [Non-Patent Document 2] “Conductivity and transparency limits of Sb-doped SnO2 grown by molecular beam epitaxy”, Martinez-Gazoni et al., Phys. Rev. B (2018), doi:10.1103 / PhysRevB.98.155308 [Non-Patent Document 3] “Highly ultraviolet transparent textured indium tin oxide thin films and the application in light emitting diodes”, Chen et al., Appl. Phys. Lett. (2017), doi:10.1063 / 1.4986452 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the transparent conductive compositions disclosed in Non-Patent Documents 1 to 3 have low transmittance to deep ultraviolet light (UV-C) with a wavelength of 280 nm or less. Deep ultraviolet light is expected to have effects such as sterilization, water purification, and air purification, and in recent years, the external quantum efficiency η ext Accordingly, the light extraction efficiency η lee In order to improve the light-transmitting properties, a substrate with a transparent electrode that is highly transparent to deep ultraviolet rays is required.

[0008] The present invention has been made in consideration of the above circumstances, and aims to provide a substrate with a deep ultraviolet light-transmitting transparent electrode, which has high transmittance to deep ultraviolet light, and a method for manufacturing a substrate with a deep ultraviolet light-transmitting transparent electrode. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention provides the following means.

[0010] [1] A substrate with a deep ultraviolet light transmitting transparent electrode according to one embodiment of the present invention comprises a transparent substrate and a transparent oxide layer formed on the transparent substrate, the transparent substrate being any substrate selected from the group consisting of a sapphire substrate, an aluminum nitride substrate, and a substrate composed of a mixed crystal of aluminum nitride and gallium nitride, the transparent oxide layer being composed of a metal oxide mainly composed of SnO2 and containing Ta element, and the amount of Ta element in the metal oxide being 0.8 atomic % or more and 7.0 atomic % or less with respect to the sum of the Sn element and the Ta element in the metal oxide.

[0011] [2] In the substrate with a deep ultraviolet light transmitting transparent electrode of the above [1], in the transparent oxide layer, the metal oxide may contain Ta element in an amount of 1.0 atomic % or more and 5.0 atomic % or less relative to Sn element.

[0012] [3] In the substrate with a deep ultraviolet light transmitting transparent electrode according to the above [1] or [2], the carrier density of the transparent oxide layer is 4.5×10 20 cm -3 It may be more than that.

[0013] [4] In the above-mentioned [1] to [3] substrate with a deep ultraviolet light transmitting transparent electrode, the transparent oxide layer may be an epitaxial layer of the metal oxide.

[0014] [5] A method for producing a substrate with a deep ultraviolet light transmitting transparent electrode according to one embodiment of the present invention includes a preparation step of preparing a transparent substrate selected from the group consisting of a sapphire substrate, an aluminum nitride substrate, and a substrate composed of a mixed crystal of aluminum nitride and gallium nitride, and a film formation step of placing a target having an elemental Ta content of 0.8 atomic % to 7.0 atomic % relative to the sum of the elements Sn and Ta opposite to the transparent substrate and performing physical vapor deposition to form a transparent oxide layer composed of a metal oxide on the transparent substrate.

[0015] [6] In the method for producing a substrate with a deep ultraviolet light transmitting transparent electrode according to the above [5], the target may be mainly composed of SnO2, and the amount of the Ta element may be 0.8 atomic % or more and 7.0 atomic % or less.

[0016] [7] In the method for producing a substrate with a deep ultraviolet light transmitting transparent electrode according to the above [5] or [6], the target may have a Ta element content of 1.0 atomic % or more and 5.0 atomic % or less.

[0017] [8] In the method for producing a substrate with a deep ultraviolet light transmitting transparent electrode according to any one of the above [5] to [7], the film forming step may be carried out by a pulsed laser deposition method. Effect of the Invention

[0018] According to the present invention, it is possible to provide a deep ultraviolet light-transmitting transparent electrode that includes a transparent conductive composition containing small amounts of constituent elements and has high transparency to deep ultraviolet light, and a method for manufacturing such a deep ultraviolet light-transmitting transparent electrode. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the configuration of a substrate with a deep ultraviolet light transmitting transparent electrode according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram for explaining a method for producing a substrate with a deep ultraviolet light transmitting transparent electrode according to one embodiment of the present invention, showing a state in which a film formation process is performed by a PLD method. [Diagram 3] FIG. 3(a) is a diagram showing the band structure of SnO2, and FIG. 3(b) is a diagram showing the band structure of the transparent conductive composition according to this embodiment. [Figure 4] 1 shows X-ray diffraction patterns of substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and substrates with electrodes of Comparative Examples 1 to 3. [Diagram 5] FIG. 5(a) is a graph showing the resistivity of the substrates with deep ultraviolet light-transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. FIG. 5(b) is a graph showing the carrier density of the substrates with deep ultraviolet light-transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. FIG. 5(c) is a graph showing the electron mobility of the substrates with deep ultraviolet light-transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. [Figure 6] 1 is a graph showing the internal transmittance spectra of the substrates with a deep ultraviolet light transmitting transparent electrode of Examples 1-1 to 1-5 and the substrates with an electrode of Comparative Examples 1 to 3. [Figure 7] 1 is a graph showing the transmittance, reflectance, and internal transmittance of the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-4 and Example 2. [Figure 8] FIG. 8(a) is a graph showing the sheet resistance and internal transmittance of the electrode-attached substrates of Examples 1-1 to 1-5, Example 2, Example 3, and Comparative Examples 1 to 6 at a wavelength of 280 nm, and FIG. 8(b) is a graph showing the sheet resistance and internal transmittance of the electrode-attached substrates of Examples 1-1 to 1-5 and Comparative Examples 1 to 6 at a wavelength of 260 nm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an example of an embodiment of the present invention will be described in detail with reference to the drawings. Note that the drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the characteristics of the present invention easier to understand. For this reason, the dimensional ratios of each component may differ from the actual ones.

[0021] [Substrate with ultraviolet light-transmitting transparent electrode] Fig. 1 is a cross-sectional view showing an example of the configuration of a substrate with a deep ultraviolet light transmitting transparent electrode according to one embodiment of the present invention. The substrate with a transparent electrode 10 shown in Fig. 1 is an optical laminate including a transparent substrate 1 and a transparent oxide layer 2 formed on the transparent substrate 1. The substrate with a transparent electrode 10 preferably includes the transparent substrate 1 and the transparent oxide layer 2.

[0022] (Transparent base material) The transparent substrate 1 is a substrate that serves as the base of the substrate 10 with a transparent electrode. The transparent substrate 1 is any substrate selected from the group consisting of a sapphire substrate, an aluminum nitride substrate, and a substrate composed of a mixed crystal of aluminum nitride and gallium nitride. When the substrate with an ultraviolet light-transmitting transparent electrode according to this embodiment is used as an LED, the transparent substrate 1 contains an aluminum nitride substrate or a mixed crystal of aluminum nitride and gallium nitride as a main component, and the transparent oxide layer 2 is formed on the transparent substrate 1 that is a part of the element. Any of a-plane, c-plane, r-plane, and m-plane transparent substrates may be used. The transparent substrate 1 is a substrate that contacts the transparent oxide layer 2, and another substrate having high transparency to deep ultraviolet light may be provided on the surface of the transparent substrate 1 opposite to the transparent oxide layer 2. For example, when the transparent substrate 1 is an aluminum nitride substrate, the aluminum nitride substrate may be formed on a sapphire substrate. For example, the aluminum nitride substrate may be formed on an a-plane sapphire substrate or a c-plane sapphire substrate. Similarly, when the transparent substrate 1 is a sapphire substrate, the sapphire substrate may be formed on an aluminum nitride substrate. For example, a c-plane sapphire substrate may be formed on a c-plane aluminum nitride substrate.

[0023] Since the transparent substrate 1 has a c-plane orientation, the transparent oxide layer 2 grown by physical vapor deposition on the transparent substrate 1 inherits the orientation of the transparent substrate 1 and grows along the c-plane.

[0024] The transparent substrate 1 is made of the above-mentioned substrate and exhibits high transmittance to deep ultraviolet light. The transparent substrate 1 is not limited to a flat substrate, but may be a substrate having a curved shape or may be a so-called flexible substrate having high flexibility.

[0025] The thickness of the transparent substrate 1 can be set arbitrarily, but is, for example, 40 μm or more and 1000 μm or less. The transparent substrate 1 is preferably a substrate that can be wound up and unwound onto a roll. When the transparent substrate 1 is a substrate that can be wound up and unwound onto a roll and the thickness of the transparent substrate 1 is within the above range, the substrate 10 with a transparent electrode can be manufactured by a roll-to-roll method, and high productivity can be achieved.

[0026] (transparent oxide layer) The transparent oxide layer 2 is made of a metal oxide mainly composed of SnO2 and containing Ta element, and the amount of Ta element in the metal oxide is 0.8 atomic % or more and 7.0 atomic % or less with respect to the sum of Sn element and Ta element in the metal oxide. The metal oxide constituting the transparent oxide layer 2 is represented by the general formula (1). Sn 100-x Ta x O2···(1) (In the formula, x satisfies 0.8≦x≦7.0.)

[0027] In the above metal oxide, the Ta element content relative to the sum of the Sn element and the Ta element is preferably 1.0 atomic % to 5.0 atomic %, more preferably 1.5 atomic % to 4.0 atomic %, and even more preferably 2.0 atomic % to 3.0 atomic %. That is, in the above formula (1), x satisfies 0.8≦x≦7.0, preferably 1.0≦x≦5.0, more preferably 1.5≦x≦4.0, and even more preferably 2.0≦x≦3.0.

[0028] As described above, the transparent oxide layer 2 is formed so as to inherit the orientation of the transparent substrate 1. The transparent oxide layer 2 is an epitaxial layer of the above-mentioned metal oxide. The transparent oxide layer 2 is configured so that, for example, there is one type of orientation in the perpendicular direction to the surface, and one to three types of orientations in the in-plane direction depending on the crystals constituting the substrate.

[0029] The resistivity of the transparent oxide layer 2 is, for example, 1.0×10 -4 Ω cm or more 5.0×10 -4Ω cm or less, 4.0×10 -4 It is preferable that the resistance is Ω·cm or less, and 3.0×10 -4 It is more preferable that the resistivity is Ω·cm or less.

[0030] The carrier density of the transparent oxide layer 2 is, for example, 2.8×10 20 cm -3 That's 4.5 x 10 20 cm -3 It is preferable that the value is 5.1×10 or more. 20 cm -3 More preferably, it is 6.0×10 or more. 20 cm -3 More preferably, the above is the case. The transparent oxide layer 2 provided on the substrate 10 with the transparent electrode according to this embodiment is manufactured by the manufacturing method described later, so that the amount of carrier density relative to the amount of doped Ta element is high, and the doped Ta element is prevented from becoming inactive. Therefore, the transparent oxide layer 2 exhibits high electrical conductivity.

[0031] The mobility of the transparent oxide layer 2 is, for example, 15 cm 2 V -1 s -1 More than 25cm 2 V -1 s -1 More than 40cm is preferable. 2 V -1 s -1 More preferably, it is 60 cm or more. 2 V -1 s -1 More preferably, it is equal to or greater than this.

[0032] The transmittance of the transparent oxide layer 2 for deep ultraviolet light having a wavelength of 280 nm is 30% or more, preferably 35% or more, more preferably 40% or more, even more preferably 50% or more, and particularly preferably 60% or more.

[0033] The thickness of the transparent oxide layer 2 is, for example, not less than 10 nm and not more than 1000 nm, and preferably not less than 50 nm and not more than 300 nm.

[0034] The figure of merit (FoM) of the substrate 10 with transparent electrodes is expressed by formula (2). In formula (2), ρ represents the resistivity of the transparent oxide layer 2, and α represents the absorption coefficient of the substrate 10 with transparent electrodes. The resistivity ρ is calculated by formula (2-1), and the absorption coefficient α is calculated by formula (2-2). In formulas (2-1) and (2-2), R represents the electrical resistance of the transparent oxide layer 2, t represents the film thickness, w represents the width, l represents the electrode spacing, and T represents the light transmittance. FoM = (ρ α) -1 (2) ρ = R × t × w / l (2-1) α=-(log e T) / t···(2-2)

[0035] The FoM of the substrate 10 with a transparent electrode for deep ultraviolet light with a wavelength of 280 nm is, for example, 0.05 or more, and preferably 0.1 or more.

[0036] [Method for manufacturing substrate with deep ultraviolet light transmitting transparent electrode] Hereinafter, a method for manufacturing a substrate with a deep ultraviolet light transmitting transparent electrode according to the above embodiment will be described. The method for manufacturing a substrate with a transparent electrode according to one embodiment of the present invention includes a preparation step of preparing a substrate selected from the group consisting of a sapphire substrate, an aluminum nitride substrate, and a substrate made of a mixed crystal of aluminum nitride and gallium nitride as a transparent substrate, and a film formation step of arranging a target having an amount of Ta element of 0.8 atomic % to 7.0 atomic % relative to the sum of the amounts of Sn element and Ta element facing the transparent substrate, and performing physical vapor deposition to form a transparent oxide layer made of a metal oxide on the transparent substrate.

[0037] (preparation process) First, a c-plane sapphire substrate or a c-plane aluminum nitride substrate is prepared. The c-plane sapphire substrate or the c-plane aluminum nitride substrate is c-plane oriented, and a substrate made of Al2O3 or AlN may be used. Alternatively, an AlN film may be formed on a c-plane or a-plane oriented Al2O3 substrate, and a c-plane aluminum nitride substrate may be formed on the c-plane sapphire substrate. Similarly, an Al2O3 film may be formed on a c-plane oriented AlN substrate, and a c-plane sapphire substrate may be formed on the c-plane aluminum nitride substrate.

[0038] (Film forming process) Next, a target containing Ta element of 0.8 atomic % or more and 7.0 atomic % or less with respect to the sum of Sn element and Ta element is placed facing the transparent substrate, and a physical vapor deposition (PVD) method is performed to form a transparent oxide layer composed of a metal oxide on the transparent substrate. The film formation process can be performed by a physical vapor deposition method such as a sputtering method, a pulse laser deposition method, or a vacuum evaporation method, and is preferably performed by a pulse laser deposition method.

[0039] 2 is a diagram for explaining a method for producing a substrate with a deep ultraviolet light transmitting transparent electrode according to an embodiment of the present invention, and shows a state in which a film formation process is performed by a PLD method. The PLD method is performed, for example, by using a pulsed laser deposition apparatus (PLD apparatus) 50. The pulsed laser deposition apparatus 50 includes, for example, a vacuum chamber 40, a sample setting stage 20, and a target setting stage 21.

[0040] A transparent substrate 1 is placed on the sample setting stage 20. The transparent substrate 1 is arranged so that the surface on which the transparent oxide layer is laminated faces the target T described later. The target T is placed on the target setting stage 21. The target T is a substrate weighed so that the amount of Ta element relative to the sum of Sn element and Ta element is 0.8 atomic % or more and 7.0 atomic % or less. The amount of Ta element relative to the sum of Sn element and Ta element in the target is preferably 1.0 atomic % or more and 5.0 atomic % or less, more preferably 1.5 atomic % or more and 4.0 atomic % or less, and even more preferably 2.0 atomic % or more and 3.0 atomic % or less. The target is, for example, a substrate in which SnO2 is doped with a predetermined amount of Ta element.

[0041] The pulsed laser deposition apparatus 50 is connected to, for example, an exhaust device 31 that reduces the pressure inside the vacuum chamber 40 and a supply device 32 that supplies a gas into the vacuum chamber 40. The exhaust device 31 is, for example, a vacuum pump. In the PLD method, for example, the exhaust device 31 evacuates the vacuum chamber 40. Next, a predetermined gas is supplied from the supply device 32 so that the inside of the vacuum chamber 40 has a predetermined atmosphere, and the exhaust device 31 adjusts the inside of the vacuum chamber 40 to a predetermined pressure. The inside of the vacuum chamber 40 is adjusted to, for example, under the supply of oxygen radicals or under the supply of an oxidizing gas such as ozone or N2O. The inside of the vacuum chamber 40 is adjusted to, for example, an oxygen partial pressure of 0.1 mTorr to 1 Torr, and preferably adjusted to 1 mTorr to 50 mTorr from the viewpoint of the film formation rate.

[0042] In the pulsed laser deposition apparatus 50, a pulsed laser L focused by a focusing lens (not shown) is irradiated onto the surface of a target T. This knocks out or evaporates constituent particles of the target T to generate a plume. The constituent particles of the target T contained in the plume are deposited on a transparent substrate 1, thereby forming a transparent oxide layer 2 on the surface of the transparent substrate 1.

[0043] The film formation step is performed, for example, while heating the transparent substrate 1. The heating temperature of the transparent substrate 1 is, for example, 200° C. or more and 900° C. or less, preferably 300° C. or more and 700° C. or less, and more preferably 450° C. or more and 650° C. or less. The transparent substrate 1 may be heated by an infrared laser (IR laser) (not shown), or may be heated by resistance heating or the like.

[0044] The target T may be in the form of a pellet or a powder.

[0045] 1 shows an example in which only one target T is provided, but a plurality of targets T may be provided. When a plurality of targets T are provided, the amount of Ta element relative to the amounts of Sn element and Ta element in the plurality of targets may be adjusted to be 0.8 atomic % or more and 7.0 atomic % or less, preferably adjusted to be 1.0 atomic % or more and 5.0 atomic % or less, more preferably adjusted to be 1.5 atomic % or more and 4.0 atomic % or less, and further preferably adjusted to be 2.0 atomic % or more and 3.0 atomic % or less.

[0046] According to the above embodiment, a transparent oxide layer 2 is formed that includes a transparent conductive composition with a small amount of constituent elements. The transparent conductive composition according to the above embodiment is formed by doping the base material SnO2 with a high concentration of Ta to introduce carrier electrons, and the Burstein-Moss shift associated with the increase in carrier electron concentration improves the transparency to deep ultraviolet light. The transparent conductive composition according to the above embodiment is formed so as to have a high carrier electron concentration, and therefore a significantly large Burstein-Moss shift is realized, resulting in high transparency to deep ultraviolet light.

[0047] FIG. 3(a) is a diagram showing a band structure of SnO2, and FIG. 3(b) is a diagram showing a band structure of the transparent conductive composition according to the present embodiment. The Burstein-Moss shift will be described with reference to FIG. 3(a) and FIG. 3(b). As shown in FIG. 3(a), SnO2 has an energy gap of E g On the other hand, as shown in Fig. 3(b), when SnO2 is doped with Ta to increase the carrier density, the carrier electrons occupy the bottom of the conduction band, and the apparent band gap (optical gap) becomes larger.

[0048] The deep ultraviolet light transmitting transparent electrode-attached substrate according to the above embodiment is suitable for display devices, light control devices and light emitting devices. Specifically, it can be used as a deep ultraviolet light transparent electrode-attached substrate suitable for LEDs that emit ultraviolet light, particularly LEDs that emit not only UV-A and UV-B but also UV-C (deep ultraviolet light). EXAMPLES

[0049] EXAMPLES Examples of the present invention will be described below, but the present invention is not limited to the following examples.

[0050] [Example 1] First, in a preparation step, a c-plane aluminum nitride substrate, which is a transparent substrate, was prepared by cleaning it with an organic solvent. The prepared c-plane aluminum nitride substrate had a flat shape and a thickness of about 0.5 mm.

[0051] Next, in the film formation step, a transparent oxide layer was formed on the c-plane aluminum nitride substrate by PLD. As the target, a pellet containing Ta element at 1 atomic % relative to the sum of Sn element and Ta element was prepared by the following procedure.

[0052] Powders of Ta2O5 and SnO2 were weighed and mixed so that the Ta element was contained at 1 atomic % relative to the sum of the Sn element and the Ta element, and then molded and heated and sintered in the air to prepare a target.

[0053] This target was placed on a target setting stage in the vacuum chamber of the PLD device. A c-plane sapphire substrate was placed on the sample setting stage so as to face the target. The sample setting stage was configured so that the substrate placed on it could be heated by an infrared laser.

[0054] Using the above PLD device, the inside of the vacuum chamber was adjusted to supply oxygen radicals, and the oxygen partial pressure was adjusted to 5 mTorr. The transparent substrate was heated to 500°C by an infrared laser, and a KrF excimer laser (pulse width approximately 20 ns) was irradiated onto the target surface from the laser inlet to form a transparent oxide layer on the transparent substrate, producing a substrate with a deep ultraviolet light-transmitting transparent electrode.

[0055] Hereinafter, the substrate with a deep ultraviolet light transmitting transparent electrode, on which a transparent conductive composition containing 1 atomic % of Ta element with respect to the sum of Sn element and Ta element was formed, produced by the above procedure, is also referred to as Example 1-1.

[0056] (Example 1-2) A substrate with a deep ultraviolet light transmitting transparent electrode was produced in the same manner as in Example 1-1, except that a target in which the amount of Ta element relative to the sum of Sn element and Ta element was 1.5 atomic % was used.

[0057] (Examples 1-3) A substrate with a deep ultraviolet light transmitting transparent electrode was produced in the same manner as in Example 1-1, except that a target in which the amount of Ta element relative to the sum of Sn element and Ta element was 2 atomic % was used.

[0058] (Examples 1 to 4) A substrate with a deep ultraviolet light transmitting transparent electrode was produced in the same manner as in Example 1-1, except that a target in which the amount of Ta element relative to the sum of Sn element and Ta element was 3 atomic % was used.

[0059] (Examples 1 to 5) A substrate with a deep ultraviolet light transmitting transparent electrode was produced in the same manner as in Example 1-1, except that a target in which the amount of Ta element relative to the sum of Sn element and Ta element was 5 atomic % was used.

[0060] Comparative Example 1 A substrate with an electrode was produced in the same manner as in Example 1-1, except that a target in which the amount of Ta element relative to the sum of Sn element and Ta element was 0.3 atomic % was used.

[0061] Comparative Example 2 A substrate with an electrode was produced in the same manner as in Example 1-1, except that a target in which the amount of Ta element relative to the sum of Sn element and Ta element was 0.6 atomic % was used.

[0062] Comparative Example 3 A substrate with an electrode was produced in the same manner as in Example 1-1, except that a target in which the amount of Ta element relative to the sum of Sn element and Ta element was 10 atomic % was used.

[0063] [Analysis of constituent phases] X-ray diffraction (XRD) was performed to analyze the constituent phases of the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. The analysis of the constituent phases by X-ray diffraction was performed under the following conditions. ·X-ray source: Cu Kα ray (output: 40kV, current: 40mA) Scanning range: 2θ=20°~90° Step time: 0.2s / step Scan speed: 6° / min Step width: 0.02° Detector: Semiconductor array detector

[0064] Fig. 4 shows X-ray diffraction patterns of the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. In Fig. 4, the locations marked with the symbol * are peaks based on the constituent phases of the substrate.

[0065] In all samples, in addition to the peaks due to the constituent phases of the substrate, the only peaks observed were the SnO2(200) peak and the SnO2(400) peak, confirming that a layer based on SnO2 had grown epitaxially on the substrate.

[0066] [Measurement of resistivity, carrier density and mobility] The resistivity, carrier density, and mobility of the substrates with a deep ultraviolet light transmitting transparent electrode of Examples 1-1 to 1-5 and the substrates with an electrode of Comparative Examples 1 to 3 were measured by the following procedures.

[0067] (resistivity) The resistivity was measured by measuring the electrical resistance by a four-terminal method for the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. Fig. 5(a) is a graph showing the resistivity of the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3.

[0068] In Fig. 5(a), the horizontal axis represents the amount (atomic %) of Ta element relative to the sum of Sn element and Ta element, and the vertical axis represents resistivity (Ω·cm). In Fig. 5(a), the results of Comparative Example 1, Comparative Example 2, Example 1-1, Example 1-2, Example 1-3, Example 1-4, Example 1-5, and Comparative Example 3 are plotted in order of the amount (atomic %) of Ta element relative to the sum of Sn element and Ta element from lowest to highest. From the results shown in Fig. 5(a), it was confirmed that the substrates with deep ultraviolet light transmitting transparent electrode of Example 1-1 to Example 1-5 exhibited excellent conductivity of 0.0004 (Ω·cm) or less at room temperature, and that Example 1-1 to Example 1-4 exhibited particularly excellent conductivity of 0.0003 (Ω·cm) or less.

[0069] The sheet resistance of the transparent oxide layer was calculated by dividing the resistivity by the thickness of the transparent oxide layer, which was measured using a stylus step gauge.

[0070] (Carrier density) The carrier density was measured by performing Hall effect measurement and four-terminal electrical resistance measurement on the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. Fig. 5(b) is a graph showing the carrier density of the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3.

[0071] The horizontal axis in FIG. 5(b) is the same as that in FIG. 5(a), and the vertical axis in FIG. 5(b) is the carrier density (cm -3 ) In FIG. 5(b), the dashed line indicates an ideal straight line in the case where one electron is emitted per doped Ta atom. The dashed line is based on the number density of Ta atoms calculated from the lattice volume of the SnO2 crystal and the amount of Ta doping. As shown in FIG. 5(b), Examples 1-1, 1-2, and 1-3 are on the dashed line, and it was confirmed that they have ideal carrier densities. In particular, Examples 1-2 to 1-5 have a carrier density of 4.0×10 20 (cm -3 ) or more, and Examples 1-3 to 1-5 show a carrier density of 5.0 × 10 20 (cm -3 In Examples 1-4 and 1-5 and Comparative Example 3, the carrier density was below the value of the dashed line, and the carrier density was 6.5×10 20 (cm -3 ) is considered to be saturated. Note that the carrier densities (×10 20 cm -3 ) were 2.9, 4.2, 5.1, 6.1, and 6.2, respectively. 20 cm -3 ) were 1.0, 1.7, and 4.0.

[0072] (Mobility) The mobility was measured by Hall effect measurement and four-terminal electrical resistance measurement for the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. Fig. 5(c) is a graph showing the electron mobility of the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. The vertical axis in Fig. 5(c) represents mobility (cm 2 V -1 s -1 As shown in FIG. 5(c), Examples 1-1 to 1-5 have a 20 (cm 2 V -1 s -1 ) or more, and Examples 1-1 to 1-4 show a mobility of 40 (cm 2 V -1 s -1 ) or more, and Examples 1-3 show a mobility of 50 (cm 2 V -1 s -1 ) or higher.

[0073] [Internal transmittance measurement] The spectra of transmittance T% and reflectance R% in the lamination direction were measured using a spectrophotometer (manufactured by JASCO Corporation, model number: V-670) for the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 and the substrates with electrodes of Comparative Examples 1 to 3. Based on the spectra of transmittance T and reflectance, the spectrum of internal transmittance τ% of the substrate with electrodes was calculated by calculating {T / (100-R)}×100.

[0074] Fig. 6 is a graph showing the internal transmittance spectra of the deep ultraviolet light transmitting transparent electrode-attached substrates of Examples 1-1 to 1-5 and the electrode-attached substrates of Comparative Examples 1 to 3. As shown in Fig. 6, it was confirmed that Examples 1-1 to 1-5 exhibit high transmittance even in the deep ultraviolet region of wavelengths of 280 nm or less. For example, for deep ultraviolet light of a wavelength of 280 nm, the internal transmittances of Examples 1-1 to 1-5 were 35% or more, the internal transmittances of Examples 1-2 to 1-5 were 40% or more, and the internal transmittances of Examples 1-4 and 1-5 were 60% or more.

[0075] Example 2 A substrate with a deep ultraviolet light transmitting transparent electrode was produced in the same manner as in Example 1-4, except that the transparent substrate was heated to a temperature of 600° C. That is, in Example 2, the amount of Ta element relative to the sum of Sn element and Ta element in the target was 3 atomic %.

[0076] Example 3 Except for changing the transparent substrate to one made of Al2O3, a substrate with a deep ultraviolet light transmitting transparent electrode was produced in the same manner as in Example 2. That is, in Example 3, c-plane sapphire was used as the transparent substrate, the amount of Ta element relative to the sum of Sn element and Ta element in the target was 3 atomic %, and the temperature at which the transparent substrate was heated during the film formation process was 600°C.

[0077] Comparative Example 4 Comparative Example 4 is experimental data on the substrate with an electrode disclosed in Non-Patent Document 1. That is, Comparative Example 4 is experimental data on the substrate with an electrode produced by forming a (101)-oriented Ta-doped SnO2 thin film on an α-Al2O3 (012)-oriented substrate by MOCVD.

[0078] As Comparative Example 4, FIG. 8 described later shows cases in which the amount of Ta element relative to the sum of Sn element and Ta element in the source gas is 4%, 6%, and 8%.

[0079] Comparative Example 4-1 corresponds to experimental data in which the amount of Ta element relative to the sum of Sn element and Ta element is 4%. Comparative Example 4-2 corresponds to experimental data in which the amount of Ta element relative to the sum of Sn element and Ta element is 6%. Comparative Example 4-3 corresponds to experimental data in which the amount of Ta element relative to the sum of Sn element and Ta element is 8%.

[0080] Comparative Example 5 Comparative Example 5 is data on the substrate with electrode disclosed in Non-Patent Document 2. That is, Comparative Example 5 is experimental data on the substrate with electrode produced by forming a (101)-oriented Sb-doped SnO2 thin film on an r-plane Al2O3 substrate. In Comparative Example 5, the amount of Sb element relative to the sum of Sn element and Sb element is adjusted to be 0.014.

[0081] Comparative Example 6 Comparative Example 6 is experimental data relating to a substrate with an electrode disclosed in Non-Patent Document 3. That is, Comparative Example 6 is experimental data in which a (111)-oriented Sn-doped In2O3 thin film, a so-called ITO thin film, is formed on a c-plane Al2O3 substrate by MOCVD to produce a substrate with an electrode.

[0082] [Internal transmittance measurement] The internal transmittance of the substrates with transparent electrodes of Examples 2 and 3 was measured by a method similar to that of Example 1 for measuring the internal transmittance of the substrate with transparent electrodes.

[0083] [Measurement of sheet resistance] In the same manner as in Example 1, the resistivity and thickness of the transparent oxide layer in the substrate with a transparent electrode of Example 2 and Example 3 were measured, and the sheet resistance of the substrate with a transparent electrode of Example 2 and Example 3 was calculated.

[0084] Fig. 8(a) is a graph showing the sheet resistance and internal transmittance of the substrates with electrodes of Examples 1-1 to 1-5 and Comparative Examples 1 to 6 at a wavelength of 280 nm, and Fig. 8(b) is a graph showing the sheet resistance and internal transmittance of the substrates with electrodes of Examples 1-1 to 1-5 and Comparative Examples 1 to 6 at a wavelength of 260 nm. In Fig. 8(a) and Fig. 8(b), the internal transmittance of the substrates with electrodes of Comparative Examples 4 to 6 and the sheet resistance of the oxide layer laminated on the substrate of the substrate with electrodes are plotted as described in non-patent literature.

[0085] 8(a) and 8(b), the figure of merit (FoM) of the substrate with a transparent electrode is shown by a dashed line. The figure of merit (FoM) is expressed by the following formula (2). FoM = (ρ α) -1 (2) In formula (2), ρ represents the resistivity of the transparent oxide layer, and α represents the absorption coefficient of the substrate with a transparent electrode. The absorption coefficient α is calculated from the internal transmittance and film thickness t using the formula τ=exp(-αt). Materials with similar figures of merit (FoM) can be said to have similar performance as transparent electrodes.

[0086] As shown in Fig. 8(a), the deep ultraviolet light transmitting transparent electrode-attached substrates of Examples 1-1 to 1-5, Example 2, and Example 3 have the same sheet resistance as the electrode-attached substrate of Comparative Example 4 in which a Ta-doped SnO2 thin film is formed on an Al2O3 substrate by MOCVD, and are confirmed to exhibit significantly superior transmittance to deep ultraviolet light of wavelengths of 280 nm and 260 nm. Therefore, the deep ultraviolet light transmitting transparent electrode-attached substrates of Examples 1-1 to 1-5 have superior figures of merit (FoM) compared to the electrode-attached substrates of Comparative Examples 4-1 to 4-3. In addition, the FoM of all the measurement results at a wavelength of 280 nm was 0.5 or less.

[0087] On the other hand, the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 have lower sheet resistance and exhibit superior conductivity compared to the substrates with electrodes of Comparative Examples 5 and 6. It was also confirmed that the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 exhibit significantly superior transmittance to deep ultraviolet light with wavelengths of 280 nm and 260 nm compared to the substrates with electrodes of Comparative Examples 5 and 6. Therefore, the substrates with deep ultraviolet light transmitting transparent electrodes of Examples 1-1 to 1-5 have superior figure of merit (FoM) compared to the substrates with electrodes of Comparative Examples 5 and 6. [Explanation of symbols]

[0088] 1: transparent substrate, 2: transparent oxide layer, 10: substrate with transparent electrode, 20: sample installation stage, 21: target installation stage, 31: exhaust device, 32: supply device, 40: vacuum chamber; 50: pulsed laser deposition device; T: target, L: pulse laser

Claims

1. A transparent substrate and a transparent oxide layer formed on the transparent substrate, The transparent substrate is any one selected from the group consisting of a sapphire substrate, an aluminum nitride substrate, and a substrate made of a mixed crystal of aluminum nitride and gallium nitride; The transparent oxide layer is made of SnO 2 and is composed of a metal oxide containing Ta element, The substrate with a deep ultraviolet light transmitting transparent electrode, wherein the amount of Ta element in the metal oxide is 0.8 atomic % or more and 7.0 atomic % or less based on the sum of Sn element and Ta element in the metal oxide.

2. 2. The substrate with a deep ultraviolet light transmitting transparent electrode according to claim 1, wherein in the transparent oxide layer, the metal oxide contains Ta element in an amount of 1.0 atomic % to 5.0 atomic % relative to Sn element.

3. The carrier density of the transparent oxide layer is 4.5×10 20 cm -3 The substrate with a deep ultraviolet light transmitting transparent electrode according to claim 2 .

4. 3. The substrate with a deep ultraviolet light transmitting transparent electrode according to claim 1, wherein the transparent oxide layer is an epitaxial layer of the metal oxide.

5. A preparation step of preparing a transparent substrate selected from the group consisting of a sapphire substrate, an aluminum nitride substrate, and a substrate made of a mixed crystal of aluminum nitride and gallium nitride; and a film formation step of: disposing a target, in which the amount of Ta element is 0.8 atomic % or more and 7.0 atomic % or less relative to the sum of the amounts of Sn element and Ta element, facing the transparent substrate, and performing a physical vapor deposition method to form a transparent oxide layer composed of a metal oxide on the transparent substrate.

6. The target is SnO 2 6. The method for producing a substrate with a deep ultraviolet light transmitting transparent electrode according to claim 5, wherein the main component is Ta and the amount of the Ta element is 0.8 atomic % or more and 7.0 atomic % or less.

7. 7. The method for producing a substrate with a deep ultraviolet light transmitting transparent electrode according to claim 5, wherein the target has an amount of Ta element of 1.0 atomic % or more and 5.0 atomic % or less.

8. The method for producing a substrate with a deep ultraviolet light transmitting transparent electrode according to claim 5 or 6, wherein the film forming step is performed by a pulsed laser deposition method.